DRY-POWDER OF CHITOSAN-COATED LIPID-CORE NANOCAPSULES CONTAINING DAPSONE: DEVELOPMENT, LASER DIFFRACTION CHARACTERIZATION AND ANALYTICAL QUANTIFICATION - Rodrigo Cé; Denise Soledade Jornada; João Guilherme Barreto De Marchi; Silvia Stanisçuaski Guterres; Adriana Raffin Pohlmann (Drug Analytical Research, 2019)
Analytical techniques are critical for ensuring physical and chemical stability of a drug both for assessing the stability of drug molecules and for quantifying and identifying the drug content in products. We proposed the development of dry-powders of lipid-core nanocapsules containing dapsone and coated with chitosan, as well as, the analytical quantification of dapsone in dry-powders with 1% and 2% (m/v) of leucine by high-performance liquid chromatography (HPLC). Size is the most relevant physicochemical property of nanoparticulated drug delivery systems. In this context, our results demonstrated that during the powders redispersion in water, could be observed that the mean particle diameters (DAP-LNC-CS-L1 and DAP-LNC-CS-L2) decreased with redispersion times increase. The spray-drying of the lipid-core nanocapsule formulations showed yields ranging from 58 ± 1.0 % (DAP-LNC-CS-L1) to 61 ± 1.5 % (DAP-LNC-CS-L2) indicating an efficient drying process. In this context, the analytical quantifications of dapsone in the dry powders of nanocapsules by HPLC showed that the dapsone content ranged from 92 ± 1.4% (DAP-LNC-CS-L2) to 95 ± 0.8% (DAP-LNC-CS-L1). Can be concluded that spray-drying process of DAP-LNC-CS-L1 and DAP-LNC-CS-L2 formulations showed an efficient aqueous dispersion of nanocapsule powders and the analytical quantification of dapsone in spray-dryed powders were higher than 90%.